Resistencia y renovación: la subversión mítica en Adiós, Ayacucho de Julio Ortega - Rivera Rodríguez, Kevin (2024)
The essay proposes that in Julio Ortega's novel Adiós, Ayacucho, a confrontation with hegemonic-Western rationality takes place from an alternative rationality that comes from the Andean worldview. The analysis is based on decolonial theory to explain the presence of this other way of thinking, through the incarnation of the protagonist, Alfonso Cánepa, in two mythical-religious figures: the Andean condemned man and the Inkarrí. It also makes use of Mijaíl Bajtín conceptualization of carnival to delve into the processes of inversion, restitution and renewal present.